1992
DOI: 10.1002/ptr.2650060307
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity of the volatile oil of Nigella sativa seeds against multiple drug‐resistant isolates of Shigella spp. and isolates of Vibrio cholerae and Escherichia coli

Abstract: The antibacterial activity of the volatile oil of Nigella sufiua seeds was studied against 37 isolates of Shigella dysenteriue I , Shigella &men, ShigeUa sonnei and ShigeUa boydu and 10 strains of Vibrio cholerae and Escherichia coli. Most of the strains were clinically resistant to ampicillin, co-trimoxazole and tetracycline. All the strains tested showed promising sensitivity to the volatile oil. The minimum inhibitory concentration (MIC) of the volatile oil for Shigellu, Vibrio and Escherichia strains teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 4 publications
(1 reference statement)
2
30
0
Order By: Relevance
“…Previously, different extraction methods, e.g., Clevenger hydrodistillation and steam distillation of seeds or their oils, have been used to obtain antibacterial active essential oil from N. sativa (2,3,10,15,19,23,(30)(31)(32)39). However, according to our results, the techniques based on steam distillation of extracted seed oils (SE-SD and SE-SFE) provide markedly more effective essential oil than do HD and SD of seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, different extraction methods, e.g., Clevenger hydrodistillation and steam distillation of seeds or their oils, have been used to obtain antibacterial active essential oil from N. sativa (2,3,10,15,19,23,(30)(31)(32)39). However, according to our results, the techniques based on steam distillation of extracted seed oils (SE-SD and SE-SFE) provide markedly more effective essential oil than do HD and SD of seeds.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the antibacterial activity of the seed was predominantly related to the volatile oil (19,30). Subsequently, the antibacterial properties of the volatile oil of N. sativa have been further examined with different types of in vitro (3,10,15,23,32) or in vivo tests (7,14).…”
mentioning
confidence: 99%
“…5 The seeds are also used as condiments, carminatives, appetizers, stimulants for menstrual flow (emmenagogue), tonics, and for increasing milk yield (galactagogue). 6 A number of studies have validated the traditional uses of N. sativa, such as antibacterial, 7 antihistamine, 8 and antioxidant effects. 9 N. sativa seed extracts and the isolated active principles, thymoquinone (TQ) and dithymoquinone showed cytotoxic activity against several tumor types and prevented tumor growth in mice [10][11][12][13] and induced telomere attrition and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the name of black cumin is sometimes given to entirely unrelated spice Nigella sativa. The crude extracts of N. Sativa were reported to have a promising effect on multi-drug resistant S. aureus and Candida albicans [10] , Shigella spp., Vibrio cholerae [15] . Production of β lactamases is the most common mechanism of resistance among the Gram-negative.…”
Section: Introductionmentioning
confidence: 99%